Engineering of Microcage Carbon Nanotube Architectures with Decoupled Multimodal Porosity and Amplified Catalytic Performance. Issue 27 (27th May 2021) - Mannering, Jamie; Stones, Rebecca; Xia, Dong; Sykes, Daniel; Hondow, Nicole; Flahaut, Emmanuel; Chamberlain, Thomas W.; Brydson, Rik; Cairns, Gareth A.; Menzel, Robert
Abstract: New approaches for the engineering of the 3D microstructure, pore modality, and chemical functionality of hierarchically porous nanocarbon assemblies are key to develop the next generation of functional aerogel and membrane materials. Here, interfacially driven assembly of carbon nanotubes (CNT) is exploited to fabricate structurally directed aerogels with highly controlled internal architectures, composed of pseudo‐monolayer, CNT microcages. CNT Pickering emulsions enable engineering at fundamentally different length scales, whereby the microporosity, mesoporosity, and macroporosity are decoupled and individually controlled through CNT type, CNT number density, and process energy, respectively. In addition, metal nanocatalysts (Cu, Pd, and Ru) are embedded within the architectures through an elegant sublimation and shock‐decomposition approach; introducing the first approach that enables through‐volume functionalization of intricate, pre‐designed aerogels without microstructural degradation. Catalytic structure–function relationships are explored in a pharma‐important amidation reaction; providing insights on how the engineered frameworks enhance catalyst activity. A sophisticated array of advanced tomographic, spectroscopic, and microscopic techniques reveal an intricate 3D assembly of CNT building‐blocks and their influence on the functional properties of the enhanced nanocatalysts. These advances set a basis to modulate structure and chemistry of functional aerogel materials independently in a controlled fashion for a variety of applications, including energy conversion and storage, smart electronics, and (electro)catalysis. Abstract : Soft‐templating of 1D carbon nanostructures provides next‐generation nanocarbon aerogels with unique microcage internal architectures and independently tuneable micro‐, meso‐, and macroporosities. The intricate aerogel microstructures are chemically modified with metal nanoparticles (Cu, Pd, Ru) through a structure‐preserving sublimation and shock‐decomposition functionalization approach. The subsequent nanoparticle‐decorated aerogels exhibit amplified catalytic performance, as well as solvent‐induced shape‐recovery behavior.